Shipboard ADCP current measurements (38 kHz) during RV MARIA S. MERIAN cruise MSM117 - Rebecca Hummels; Robert Kopte; Tim Fischer; Franz Philip Tuchen (PANGAEA, 2024)
Current velocities of the upper water column along the cruise track of R/V Maria S. Merian cruise MSM117 were collected by a vessel-mounted 38 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 6.0 m below the water line. The instrument was operated in two different configurations: 1) broadband mode with 32 m bins and a blanking distance of 16 m, with a total of 50 bins, 2) narrowband mode with 32 m bins and a blanking distance of 16 m, with a total of 50 bins. Beam velocities as recorded by the data acquistion software VmDAS were transformed to ship coordinates and after merging with the navigation data from the ship extquotesingles Motion Reference Unit and Global Positioning systems into earth coordinates. Single-ping data were screened for bottom signals and, where appropriate, a bottom mask was manually processed. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. Data post-processing included water track calibration of the misalignment angle (configuration 1: 0.3196° +/- 0.8714°, configuration 2: 0.3603° +/- 0.6433°) and scale factor (configuration1: 1.0007 +/- 0.0151, configuration 2: 1.0024 +/- 0.0107) of the Ocean Surveyor signal. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on following threshold criteria: abs(UC) or abs(VC) > 2.0 m/s, rms(UC_z) or rms(VC_z) > 0.3.